2023
DOI: 10.1182/bloodadvances.2022008790
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of nivolumab combined with ibrutinib in patients with diffuse large B-cell Richter transformation of CLL

Abstract: Richter transformation (RT) is a rare complication of CLL with dismal outcomes. Upregulation of PD-1/PD-L1 drives immunological evasion in patients with RT. We hypothesized if combining nivolumab, a PD-1 blocking antibody, with the BTK inhibitor (BTKi) ibrutinib could potentiate tumor-cell killing. We conducted an investigator-initiated phase 2 clinical trial to assess the efficacy of combined nivolumab and ibrutinib in patients with diffuse large B-cell lymphoma (DLBCL) RT and CLL. Patients included were ≥18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…To improve upon single agent responses, investigations of checkpoint blockade in combination with other drugs are ongoing. A recently reported clinical trial evaluating the combination of nivolumab with ibrutinib demonstrated a 42% ORR with a median OS of 13 months (n = 24) and very few toxicities [ 66 ]. Another investigational strategy involving the combination of pembrolizumab, umbralisib (a PI3Ki) and ublituximab (a type I CD20 antibody) has shown promising initial results with an ORR of 50% in 4 relapsed/refractory RT patients with ongoing remissions of greater than 7 months [ 67 ].…”
Section: Inhibitors Of Program Cell Death Receptor-1 (Pd-1) and Its L...mentioning
confidence: 99%
“…To improve upon single agent responses, investigations of checkpoint blockade in combination with other drugs are ongoing. A recently reported clinical trial evaluating the combination of nivolumab with ibrutinib demonstrated a 42% ORR with a median OS of 13 months (n = 24) and very few toxicities [ 66 ]. Another investigational strategy involving the combination of pembrolizumab, umbralisib (a PI3Ki) and ublituximab (a type I CD20 antibody) has shown promising initial results with an ORR of 50% in 4 relapsed/refractory RT patients with ongoing remissions of greater than 7 months [ 67 ].…”
Section: Inhibitors Of Program Cell Death Receptor-1 (Pd-1) and Its L...mentioning
confidence: 99%
“…Therefore, effective therapeutic alternatives represent an unmet clinical need for MCL. In this scenario, the combination of ibrutinib with the anti-PD1 nivolumab has been studied in clinical trials [37] in several types of NHL but not in MCL, showing good results in CLL Richter transformation [38]. Thus, we analyzed the efficacy of this combination compared to ibrutinib in the PDLS system.…”
Section: Patient-derived MCL Spheroids Engage Immune Activation In Re...mentioning
confidence: 99%
“…In this scenario, the combination of ibrutinib with the anti-PD1 nivolumab has been studied in clinical trials 38 in several types of NHL but not in MCL, showing good results in CLL Richter transformation. 39 Thus, we analyzed the e cacy of this combination compared to ibrutinib in the PDLS system. As shown in Fig.…”
Section: Patient-derived MCL Spheroids Engage Immune Activation In Re...mentioning
confidence: 99%